ALLOMAS ON SPIRITUAL AND MORAL ASSIGNMENT - Xodjaeva Dilorom Yunusovna (Scholar Express Journal, 2022)
The article analyzes the views of the great thinkers of the Middle East, such as Abu Nasr Farobi, Jalaliddin Rumi, Alisher Navoi, on human perfection, education and spiritual and moral progress from a philosophical point of view.
Keywords: Man; Humanity; Spirituality; Enlightenment